Performance is no proxy for genetic quality: trade-offs between locomotion, attractiveness, and life history in crickets - Lailvaux, Simon P; Hall, Matthew D; Brooks, Robert C (Ecology (Durham), 2010)
The genetic relationships among traits contributing to overall fitness are an important subject of inquiry because such relationships influence how suites of traits respond to selection. Within the field of sexual selection, these relationships are also of interest for assessing whether any given trait can be used as a proxy for total fitness. A growing number of studies have demonstrated close links between whole-organism performance traits and determinants of individual fitness; however, an understanding of the genetic relationships between performance and important aspects of genetic quality is currently lacking. We present the results of a quantitative genetic study in which we estimate covariation between a locomotor performance trait (maximal jumping ability), calling effort, sexual attractiveness, and life-history traits in male Teleogryllus commodus crickets. We show that the major axis of genetic variation (gmax) is characterized by a contrast between jump performance and life-history traits associated with mating success. Moreover, two additional axes of significant multivariate genetic variation exist, each characterized by strong contrasts among traits. These results argue against the existence of a single axis representing genetic quality, favoring instead the idea that resource allocation strategies shape multiple dimensions of genetic quality through trade-offs among key life-history traits, including performance.